Co-processing of ETP Sludge of ACC Madukkarai - Ulhas2, Gautam S.P.3, Bundela Pusppendra. S.1*, Parlikar (Recent Research in Science and Technology, 2011)
M/S Ford India private Limited, it is one of the leading vehicles manufactures generated large amount chemical sludge and oil wastes during its manufacturing operations. The hazardous waste generates from ford company was co-processed during the trial burn conducted at ACC Madukkarai cement works. Co-processing of ETP- sludge the cement kiln is the most scientific and environmentally sound manner without influencing emissions on partial replacement of traditional fuel. Co-processing in cement kiln ranks higher in the waste management hierarchy, when compared to other disposal options such as incineration and landfill, Co-processing does not leave behind any residue that might have harmful impacts on the environment. Thus it is an ecologically sustainable solution for waste management. All the results are under permissible limit as per Central Pollution Control Board for the common hazardous waste incinerators.